Karakteristik Pasien Otitis Media Akut - Tan’im Arief; Nia Triswanti; Fatah Satya Wibawa; Galang Aprianda Rulianta Adha (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Background: Acute Otitis Media (AOM) is an inflammatory disease of the middle ear that has been experienced for less than 3 weeks. Objective To find out the characteristics of acute media otitis patients. Methods: This study uses descriptive quantitative, the population is a patient recorded in the medical records. Sampling technique using Slovin formula. Research results: Of the 40 samples studied obtained frequency of the 40 samples studied, was found that the most age was the age range 21-40 years and 41-60 years as many as 13 people (32.5%). For the most gender, 22 people were male (55%). For the distribution of the frequency of pain, the most common was mild pain as many as 20 people (50%). The main complaint experienced by patients with acute otitis media was decreased hearing which was obtained by 26 people (65%) Conclusion: From this study, cases of acute otitis media were found for the most age range in the adult age range. For sex, it was mostly found in the male gender. For the acute otitis media pain scale, the most based on the pain scale was found mostly in mild pain. The most common symptom is decreased hearing